Empowering Indonesian Migrant Workers to Prevent and Manage Stroke through Personal Social Responsibility (PSR) in Penang, Malaysia - Ganiem, Leila Mona; Saragih, Nurhayani; Hartono, Sri (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
Stroke is a leading cause of death in Indonesia and the world.  Indonesian migrant workers (TKI) in Malaysia, also face high risks due to unhealthy lifestyles, chronic stress, and limited healthcare access.  This community service program addresses these challenges by empowering TKI through Personal Social Responsibility (PSR), fostering cooperation (gotong royong) to enhance collective well-being. The program focuses on improving health literacy through tailored stroke prevention education and enabling the community to take ownership of health initiatives via strategic communication and peer-led actions. Activities include interactive workshops, health ambassador training, development of culturally sensitive educational materials, health screenings, and peer support networks. These initiatives equip participants with essential knowledge, encourage proactive health behaviors, and promote sustainable stroke prevention strategies. The program has successfully improved health literacy among 80% of participants and trained 24 health ambassadors who actively disseminate information and advocate for healthier lifestyles. These measurable outcomes align with the program’s objectives of fostering a resilient and health-conscious community. By integrating PSR principles, this initiative strengthens the resilience of the TKI community, fostering a culture of shared responsibility in stroke prevention and overall health improvement.ABSTRAKStroke merupakan penyebab kematian utama di Indonesia dan dunia. Tenaga Kerja Indonesia (TKI) di Malaysia juga menghadapi risiko tinggi akibat gaya hidup tidak sehat, stres kronis, dan terbatasnya akses layanan kesehatan. Program pengabdian masyarakat ini menjawab tantangan tersebut dengan memberdayakan TKI melalui Personal Social Responsibility (PSR), memupuk kerja sama (gotong royong) untuk meningkatkan kesejahteraan kolektif. Program ini berfokus pada peningkatan literasi kesehatan melalui edukasi pencegahan stroke yang disesuaikan dan memungkinkan masyarakat untuk mengambil kepemilikan atas inisiatif kesehatan melalui komunikasi strategis dan tindakan yang dipimpin oleh rekan sebaya. Kegiatannya meliputi lokakarya interaktif, pelatihan duta kesehatan, pengembangan materi edukasi yang peka budaya, skrining kesehatan, dan jaringan dukungan sebaya. Inisiatif-inisiatif ini membekali peserta dengan pengetahuan penting, mendorong perilaku kesehatan proaktif, dan mempromosikan strategi pencegahan stroke yang berkelanjutan. Program ini telah berhasil meningkatkan literasi kesehatan di antara 80% peserta dan melatih 24 duta kesehatan yang secara aktif menyebarluaskan informasi dan mengadvokasi gaya hidup yang lebih sehat. Hasil yang terukur ini sejalan dengan tujuan program untuk membina masyarakat yang tangguh dan sadar kesehatan. Dengan mengintegrasikan prinsip-prinsip PSR, inisiatif ini memperkuat ketahanan komunitas TKI, menumbuhkan budaya tanggung jawab bersama dalam pencegahan stroke dan peningkatan kesehatan secara keseluruhan.